The Most Effective Way of Enforcing International Criminal Law - Ahmad Alsharqawi,; AlKhseilat, Abdullah Ahmed; Alsharqawi, Abed Alkarim (International Journal of Psychosocial Rehabilitation, 2020)
The International Criminal Court (ICC or ICCt) is an intergovernmental organization and international tribunal that sits in The Hague, Netherlands. The ICC has jurisdiction to prosecute individuals for the international crimes of genocide, crimes against humanity, war crimes, and crimes of aggression. A crime is an act committed or omitted in violation of Public Law, but the most challenges before ICC about the Implementation and enforcing international criminal law.This research will answer this question What is the most effective way of enforcing international criminallaw? This research studies the effectiveness of the international criminal law. It will study the role of the individual in the international criminal law. It will research the origin and effective set up of the international criminal court as a means to settle international crimes against humanity. It will discuss the drawbacks of the current system and suggest measures to make the international criminal law as an effective tool in the international criminal law.